2019
DOI: 10.1002/jcb.28928
|View full text |Cite
|
Sign up to set email alerts
|

Tid1‐S attenuates LPS‐induced cardiac hypertrophy and apoptosis through ER‐a mediated modulation of p‐PI3K/p‐Akt signaling cascade

Abstract: Myocardial dysfunction is clinically relevant? repercussion that follows sepsis. Tid 1 protein has been implicated in many biological process. However, the role of Tid 1 in lipopolysaccharide (LPS)‐induced cardiomyocyte hypertrophy and apoptosis remains elusive. In the current research endeavor, we have elucidated the role of Tid1‐S on LPS‐induced cardiac hypertrophy and apoptosis. Interestingly, we found that overexpression of Tid1‐S suppressed TLR‐4, NFATc3, and BNP protein expression which eventually led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The binding of E2 and ERα exists in the cell membrane and nucleus, 56 which can be divided into genomic oestrogen signalling pathways and non‐genomic oestrogen signalling pathways. E2 diffuses through the cell membrane, and when it encounters palmitoylated‐ERα binding on the cell membrane, the ligand (E2) binds to the receptor (ERα), which can activate various cytoplasmic enzymes through non‐genomic interactions, including mediating the PI3K‐Akt pathway to regulate cell proliferation and survival 56–58 . In addition, the MAPK/ERK1/2 signal transduction pathway can also be activated to regulate tumour growth and progression 56,59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…The binding of E2 and ERα exists in the cell membrane and nucleus, 56 which can be divided into genomic oestrogen signalling pathways and non‐genomic oestrogen signalling pathways. E2 diffuses through the cell membrane, and when it encounters palmitoylated‐ERα binding on the cell membrane, the ligand (E2) binds to the receptor (ERα), which can activate various cytoplasmic enzymes through non‐genomic interactions, including mediating the PI3K‐Akt pathway to regulate cell proliferation and survival 56–58 . In addition, the MAPK/ERK1/2 signal transduction pathway can also be activated to regulate tumour growth and progression 56,59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…When LPS stimulates H9C2 cells (rat embryonic cardiomyoblasts), the overexpression of miR-146a suppresses apoptosis and helps attenuate myocardial depression ( An et al, 2018 ). Chao et al found that the overexpression of Tid1-S can enhance ER-α to activate p-PI3K/p-Akt, attenuating LPS-induced apoptosis in H9C2 cells ( Chao et al, 2019 ). In recent years, as the understanding of m 6 A modification has gradually deepened, studies have found that m 6 A modification plays an important role in the process of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cardiac complications induced LPS by are associated with cardiac apoptosis (11), as well as with the overexpression of pro-inflammatory cytokines (12). In addition, furthermore, the pro-inflammatory cytokinin activation induced by LPS is triggered by the nuclear factor-κB (NF-κB), which can stimulate the overexpression of multiple pro-inflammatory cytokines, thereby affecting myocardial function (13).…”
Section: Original Articlementioning
confidence: 99%